An analysis of Nigeria’s petroleum subsidy removal as a neocolonial and dependency tool - Okafor , Joachim Chukwuma; Oladejo, Abiodun Omotayo (University of Nigeria Journal of Political Economy, 2026)
Upon assuming office on May 29, 2023, Nigerian President Bola Tinubu declared that the petrol subsidy regime, which had been in place for over three decades, had come to an end. Immediately, petrol marketers adjusted the pump price to reflect the new reality, leading to high transportation costs and hyperinflation. Using a documentary approach and post-colonial state theory, we argue that the President’s progressive ideal "allow the poor to breathe", which formed the core of his election campaign, has been diminished by removing the subsidy on the pump price of petrol. Although the removal of the subsidy has deepened poverty in Nigeria, international finance agencies such as the World Bank and the International Monetary Fund (IMF) - which have recommended the policy switch, have praised it. The policy switch from the progressive ideal of allowing the poor (sic) to breathe to removing the fuel subsidy - without first increasing Nigeria’s downstream sector’s capacity - underlies a desire to kowtowing to the policy prescriptions of the World Bank and IMF rather than securing the living conditions of vulnerable Nigerians.